Comparing Stenting with Medical Therapy Versus Medical Therapy Alone in Patients with Intracranial Atherosclerotic Stenosis: A Current Systematic Review and Meta-Analysis - Khalid Bin Aziz; Hussam Alhathlol; Fahad Bin Aziz; Mohammed Alshammari; Mohammed Ali Alhefdhi; Abdulrahman M. Alrasheed; Nawwaf Alfayez; Thamer S. Alhowaish (Clinics and Practice, 2025)
Background: Intracranial atherosclerotic stenosis (ICAS) is a significant cause of ischemic stroke worldwide, with high recurrence rates despite optimal medical therapy. While endovascular stenting has been proposed as an adjunctive treatment, its clinical benefit remains controversial as a first line therapy. Objective: To evaluate the efficacy and safety of stenting plus medical therapy (STN+MT) compared to medical therapy alone (MT) in patients with symptomatic ICAS through a systematic review and meta-analysis of randomized controlled trials (RCTs). Methods: We systematically searched PubMed, Web of Science, the Cochrane Library, Embase, Scopus, and EBSCO for RCTs comparing STN+MT with MT in adult patients with symptomatic ICAS. Primary outcomes included transient ischemic attack (TIA), stroke, intracerebral hemorrhage (ICH), and death at 30 days and 1 year. Pooled risk ratios with 95% confidence intervals were calculated using random-effects or fixed-effects models as appropriate. Meta-regression was conducted to assess effect modification by study-level characteristics. Results: Four trials comprising 990 patients were included. STN+MT was associated with significantly higher 30-day risk of stroke and ICH compared to MT alone. No significant differences in TIA, stroke, ICH, or death were found at 1 year. Meta-regression revealed no significant effect modifiers, suggesting consistent findings across subgroups. Conclusions: Our meta-analysis consolidates the evidence that intracranial stenting as a first line therapy offers no significant advantage over medical therapy in preventing stroke in symptomatic ICAS, while it does pose added early risks. This holds true across different trials, patient demographics, and clinical scenarios examined. The consistency of this message across multiple RCTs provides a high level of evidence to guide practice. At present, aggressive medical therapy alone should be the default management for most patients. Endovascular intervention should be reserved for clinical trial settings or carefully selected salvage cases, until and unless new evidence emerges to change the risk–benefit calculus such as the promising use of balloon angioplasty in the BASIS trial.